The Interest Considered to Criminalize Fraudulent Bankruptcy ــــ an Analytical Study in Iraqi Law - Abdul Rahman Dakhil Nahi (Journal of Legal Sciences, 2024)
The commercial business is the subject of many legal provisions، as legislation and jurisprudence have been concerned with determining everything related to this business and the duties imposed on those who practice it، among these legal provisions regarding commercial bankruptcy، especially those that are under fraudulent methods. Fraudulent commercial bankruptcy، despite the fact that at first glance it represents a harsh system in terms of the provisions and rules that it came up with، but the protection of commercial credit and work to perpetuate trust among dealers in the commercial environment prompted the Iraqi legislator to seek to identify the features of this system، which is characterized as a preventive system aimed at preserving the financial achieves deterrence in the category of criminalization (merchant) or commercial company the importance of research by reviewing and analyzing the jurisprudence and legal texts that have addressed the specter of commercial bankruptcy and the financial and administrative failure that affects the merchant and the extent of their response to the Iraqi legislative system، and the importance of research lies through exploring the ways that lead to these risks and their legal outlets and ways to address and activate the elements of predicting commercial bankruptcy.